Challenges faced by Malian EFL Students in using English at ULSHB: a Case Study of Prepositions on, and, at - Araba Moussa SAMAKE (Akofena)
Abstract: This study examines the challenges faced by first-year English students at Université des Lettres et des Sciences Humaines de Bamako (ULSHB) in using the English prepositions "in," "on," and "at." Given the global significance of English, proficiency in its use is critical, yet French-speaking Malian students encounter difficulties due to differences between English and French prepositional systems. The study involved 60 students who completed a 15-minute test consisting of sentences requiring the insertion of the appropriate prepositions through a questionnaire. The results reveal a mix of positive and negative transfer from French, affecting students' accuracy. Notably, the highest accuracy was observed in sentences where English prepositional use aligns with French patterns, such as in expressions of time. In contrast, lower accuracy rates were found in contexts where prepositional use diverges significantly between the two languages. The quantitative method was adopted in this study. The findings show that we need specific teaching methods to help students better understand and use English prepositions. The study recommends focusing on how English and French prepositions differ and giving students practice in real-life situations to improve their skills. Keywords: preposition, EFL student, lingua franca, transfer, ULSHB